Innovative leadership and its influence on the creative behavior of academic leaders in Jordanian universities (Journal of Namibian Studies : History Politics Culture, 2023)
The study identifies innovative leadership and its influence on the creative behavior of the communityacademic leaders in Jordanian universities. It uses the descriptive analytical approach. The nature of the community work is the following leadership positions: Vice President, Dean of Faculty, Vice Dean, and Head of Department, which numbered (1131) academic leaders, and consisted of (399) academic leaders.The study showed a statistically significant effect of innovative leadership in the creative behavior of academic leaders in Jordanian public universities with no such differences in the responses of the sample members in the level of innovative leadership and creative behavior attributed to gender variables, college specialization, academic rank and nature of work. Further, the responses are statistically differentin the creative behavior because ofthe nature of the work and in favor of the assistant dean. In this work, * indicates statistical significance at the significance level (α≤0.05) and ** is statistical significance at significance level (α≤0.01).